Sirolimus versus tacrolimus for systemic lupus erythematosus treatment: results from a real-world CSTAR cohort study - Jiang, Nan; Li, Mengtao; Zhang, Hongfeng; Duan, Xinwang; Li, Xiaofeng; Fang, Yongfei; Li, Hongbin; Yang, Pingting; Luo, Hui; Wang, Yanhong; Peng, Liying; Zhao, Jiuliang; et al. (Lupus science & medicine, 2022)
ObjectiveThe effectiveness and safety of sirolimus for SLE treatment have been shown in some uncontrolled studies. However, a comparison of sirolimus with other classic immunosuppressants has not been reported. We conducted the study to compare the effectiveness and safety of sirolimus versus tacrolimus for SLE treatment.MethodsA real-world cohort study was conducted. Patients with clinically active SLE who were prescribed sirolimus or tacrolimus were enrolled. Propensity score matching was used to ensure equivalent disease conditions and background medications. SLE disease activity indices, serological parameters, steroid doses, modification of other immunosuppressants, renal effectiveness and adverse events were compared between the two groups at 3-month, 6-month, 9-month and 12-month follow-up visits.ResultsData from 52 patients in each of the sirolimus and tacrolimus groups were analysed. Indices regarding the effectiveness of sirolimus, including Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) scores, physician’s global assessment (PhGA) scores, and proportion of patients with SLEDAI-2K reduction of ≥4 and PhGA increase of <0.3, were equivalent to those of tacrolimus at all follow-up timepoints (all p≥0.05). Greater improvements in complement levels were observed in the sirolimus group at 3 and 6 months. Higher percentages of patients with prednisone doses ≤7.5 mg/day were observed in the sirolimus group at all timepoints. Seventeen adverse events in the sirolimus group were recorded. None was severe or led to drug discontinuation.ConclusionsOverall, sirolimus was as effective as tacrolimus in the treatment of SLE. Sirolimus had better effects on serological improvement and glucocorticoid tapering. Sirolimus was well tolerated in patients with SLE.